Case report: Successful treatment of refractory immune thrombocytopenia in chronic lymphocytic leukaemia with venetoclax monotherapy - Woo, Timothy; Carter, Matthew; Follows, George; Patten, Piers EM. (Frontiers in Oncology, 2023)
In chronic lymphocytic leukaemia (CLL), immune dysregulation is common and can manifest as immune thrombocytopenia (ITP). Corticosteroids are the mainstay for front-line management of CLL-associated ITP. Therapy-refractoriness represents a clinical challenge and is an indication to commence CLL-directed treatment, historically with anti-CD20 antibody-based chemoimmunotherapy. There is a small but growing body of evidence supporting the use of Bruton tyrosine kinase (BTK) inhibitors in this setting, but not the B-cell lymphoma-2 inhibitor, venetoclax. Here, we describe two cases of refractory ITP in patients with CLL who successfully achieved and sustained complete remission with fixed-duration venetoclax monotherapy. Responses were rapid and durable, and not explained by the concomitant use of an anti-CD20 antibody. This supports a dual role for single-agent venetoclax in managing active CLL and associated ITP, as an alternative to BTK inhibitors and anti-CD20 monoclonals.